Pengaruh Ukuran Perusahaan, Listing Age, Profitabilitas dan Reputasi KAP terhadap Corporate Internet Financial Reporting (CIFR) pada Bank Konvensioal Tahun 2018 - 2020 - Muhammad Raihan Hendasri; Salma Taqwa (Universitas Negeri Padang, 2022)
This study aims to determine the effect of firm size, Listing age, profitability and Reputation of audit firms on Corporate Financial Reporting (CIFR). The independent variables are company size, company age, profitability, audit firm reputation. While the dependent variable is CIFR. The sample used is Conventional Banks on the Indonesia Stock Exchange for the period 2018-2020. The statistical method used is multiple linear regression analysis. The results showed that firm size, profitability and reputation of the audit firm had no significant negative effect on CIFR, while firm age had a significant positive effect on CIFR.